Cytotoxic activity and apoptotic induction of some edible Thai local plant extracts against colon and liver cancer cell lines - Pornhathai Putthawan; Supattra Poeaim; Varipat Areekul (My University, 2018)
Purpose: To evaluate eight edible Thai local plant extracts (Camellia sinensis, Careya sphaerica, Cratoxylum formosum, Eleutherococcus trifoliatus, Ficus auriculata, Persicaria odorata, Schima wallichii, and Vaccinium sprengelii) against colon and liver cancer cell lines. Methods: The 80 % ethanol plant extracts were screened for cytotoxic activity against human colon adenocarcinoma (HT-29) and human hepatocellular carcinoma (HepG2) cells by MTT assay. The 50 % cytotoxic activity concentration (CC50) was then determined. Apoptotic cell death was observed by inverted microscopy and DNA fragmentation using agarose gel electrophoresis. Results: P. odorata and S. wallichii extracts showed strong cytotoxic activity, with the latter exhibiting more potent cytotoxic activity than the former. The CC50 value of S. wallichii extract was 453 and 367 µg/mL against HT-29 and HepG2 cells, respectively. In contrast, P. odorata extract showed CC50 value of 775 µg/mL against HT-29 and 1665 µg/mL against HepG2 cells. Microscopic observations indicate that the degree of morphological changes was concentration-dependent. The cell lines treated with both plant extracts displayed apoptosis. Conclusion: The two plant extracts have high potentials for medicinal use in colon and liver cancer management. However, further studies are needed to isolate the active compounds responsible for the cytotoxic activities. Keywords: Edible Thai local plants, Cytotoxic activity, Apoptotic induction, Colon cancer, Liver cancer
Keywords: MTT assay; Natural product bioactivities and synthesis